Biologically Active Natural Products: Agrochemicals - Cutler, Horace G (CRC Press, 2009)
Natural products that have both plant growth regulatory properties and pharmaceutical properties are examined in this book. This is the first and most up-to-date text linking agrochemistry and pharmaceutical chemistry in an easy to read presentation for practitioners in both fields.